Numerical computation of PDE formed characterizing thermal rheology of Cu/Al2O3/TiO2 ternary nanoparticles flow between coaxial cylinders - Noreen Sher Akbar; M.Fiaz Hussain; Dennis Ling Chuan Ching; Muhammad Farooq; Ilyas Khan (International Journal of Thermofluids)
This study discussed the thermal performance of magnetohydrodynamic convective flow carrying ternary nanoparticles. The movement of ternary hybrid nanofluids along an ambient porous surface between dual coaxial cylinders is modeled considering laminar flow, considering uniform permeability and an applied magnetic field. As no article discussed the application of ternary nanofluid in Coaxial Cylinder. The quadratic thermal effects in the flow of electrically conducting fluid containing ternary nanoparticles between coaxial porous cylinders have diverse applications, spanning from industrial processes improvement to advancements in environmental engineering, nanofluidic devices, biomedical engineering, enhanced oil recovery, advanced cooling technologies, electro fluidic systems, and heat exchanger design. The governing partial differential equations associated with the single-phase simulation of ternary nanoparticles, including morphological effects, are analyzed. The numerical solution using a fourth-order Runge-Kutta method alongside the Shooting technique with MATLAB software is applied to obtain results for parameters such as nanoparticles' volume fraction, permeability, and expanding/contracting factors for velocity profile and temperature profile. Comparison tables are generated for different ternary nanoparticles, illustrating Nusselt number and shear stress. The velocity profile increases with higher permeability numbers and the influence of magnetohydrodynamics. Enhanced thermal performance is observed under normal temperature conditions due to nanoparticle variations. The magnetic field exhibits a contrary influence on flow and temperature. The reduction parameter significantly affects thermal upsurges in the thermal field. A decrease in shear stress occurs for expanding cases, while an increase in the thermal system is evident with rising nanoparticle concentrations. Elevated temperatures are observed with increased thermophoresis variables. Further it is seen temperature profile rises 10 % with the rise in nanoparticle volume fraction and 2 % with the rise in Pr number.